2018
DOI: 10.1093/cvr/cvy208
|View full text |Cite
|
Sign up to set email alerts
|

Modelling inherited cardiac disease using human induced pluripotent stem cell-derived cardiomyocytes: progress, pitfalls, and potential

Abstract: In the past few years, the use of specific cell types derived from induced pluripotent stem cells (iPSCs) has developed into a powerful approach to investigate the cellular pathophysiology of numerous diseases. Despite advances in therapy, heart disease continues to be one of the leading causes of death in the developed world. A major difficulty in unravelling the underlying cellular processes of heart disease is the extremely limited availability of viable human cardiac cells reflecting the pathological pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 212 publications
(282 reference statements)
1
35
0
Order By: Relevance
“…Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have created new perspectives in many fields, including developmental biology, drug testing, safety pharmacology, and disease modelling. 1 The implementation of cellular models for in vitro safety pharmacology has reduced drug attrition due to proarrhythmic effects. 2 Concurrently, the approval rate of new drugs fell, 3 indicating the need for more specific proarrhythmic tests and biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have created new perspectives in many fields, including developmental biology, drug testing, safety pharmacology, and disease modelling. 1 The implementation of cellular models for in vitro safety pharmacology has reduced drug attrition due to proarrhythmic effects. 2 Concurrently, the approval rate of new drugs fell, 3 indicating the need for more specific proarrhythmic tests and biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…In LQTS2 iPSC-CM models, an increase of the action potential duration (APD) has been observed [ 144 ]. The phenotype has been recapitulated in vitro: an alteration of KCNH2 function, due to the presence of gene mutations, led to a decrease of the I Kr current and the development of arrythmias [ 145 ]. In 2013, Bellin et al, reported a mutation (N996I) in KCNH2 responsible for a moderate growth of the APD without early-after depolarization (EAD) [ 142 ].…”
Section: Ipscs In Cardiac Disease Modelingmentioning
confidence: 99%
“…This is particularly beneficial for therapies targeting the heart as patient-derived hiPSCs can easily be induced to differentiate into cardiomyocytes. These induced cardiomyocytes (iCMs) can then be used to explore the cardiac-specific effects of treatment on specific patient genetic backgrounds [60,61]. Advances in genome editing have revolutionized the cardiovascular field, allowing the creation of isogenic cell lines differing only at the locus of interest.…”
Section: Creating Disease Modelsmentioning
confidence: 99%